Seasonality and sociality in tree sparrows "Passer montanus" - Mónus, Ferenc; Barta, Zoltán (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Despite the fact that the tree sparrow is often the object of behavioural studies and is a well?investigated species, no specific investigations were performed on the seasonal and daily pattern of the changes in flock size. Several observations suggest clear seasonal and daily periodicity of social organisation, and in connection with these changes, a similar periodicity in flock sizes. In this paper we present the results of a three-year observational study on the flock sizes of a suburban tree sparrow population.
Keywords: wróblowe; ornitologia